Non-participation of female sex workers in HIV sentinel surveillance 2017 in the central zone, and its effect on observed HIV prevalence rate - Shashi Kant; Ayush Lohiya; Sanjay Kumar Rai; Puneet Misra; S Venkatesh; Research TeamFNx01 (Wolters Kluwer Medknow Publications, 2020)
Background: During HIV sentinel surveillance (HSS) 2017 round, the sampling strategy to recruit female sex workers (FSWs) was changed from consecutive to random sampling. This may affect the participation and HIV positivity rates among FSWs. Objective: The objective of this study is to estimate the nonparticipation rates among FSWs and its effect on the observed HIV prevalence rate during HSS-2017. Methods: The data were collected from FSW sentinel sites located in the states of Delhi, Jharkhand, Uttar Pradesh, and Uttarakhand (Central Zone). The HIV positivity rate among FSWs who participated in HSS-2017 was compared with the HIV positivity rate of those who did not participate. HIV status of the participants was obtained from HSS-2017 data. The master list of participating targeted intervention sites was accessed to obtain the last known HIV status of the eligible nonparticipants. Results: Nonparticipation rate of FSWs from the central zone during HSS2017 was 10.8%. The HIV positivity rate among nonparticipant FSW was four times and six times higher in Delhi and UP, respectively. Conclusion: Selective nonparticipation of eligible FSWs might have led to the underestimation of the HIV positivity rate in the central zone during the HSS-2017 round.